Pengaruh Struktur Good Corporate Governance Terhadap Ketepatan Waktu Pelaporan Keuangan - Ratih Silvirianiti; tumirin tumirin (Journal of Culture Accounting and Auditing, 2022)
The purpose of this study is to examine the effect of corporate governance structure consisting of the Board of Directors, Independent Commissioners, Audit Committee and Audit Opinion on the timeliness of financial reporting. The population used in this study were all manufacturing companies listed on the Indonesia Stock Exchange (IDX), during 2016-2018. Total samples tested in this study were 105 samples that met the criteria as research samples. The analysis technique used is logistic regression analysis. The results showed that the Independent Commissioner had a negative effect on the timeliness of financial reporting. Whereas the Audit Committee and Audit Opinion do not affect the timeliness of financial reporting. The results of this study indicate that the timeliness of corporate financial reporting is influenced by the Board of Directors and Independent Commissioners